Facile fabrication of alveolate Cu2−xSe microsheets as a new visible-light photocatalyst for discoloration of Rhodamine B1. Issue 48 (26th November 2018) - Zhong, Wenwu; Shen, Shijie; Feng, Shangshen; Lin, Zhiping; Wang, Zongpeng; Fang, Baizeng
Abstract : A new photocatalyst, alveolate Cu2− x Se microsheets, is developed, which reveals superior photocatalytic discoloration of Rhodamine B. Abstract : A new porous material, alveolate Cu2− x Se microsheets, was synthesized through a simple one-step solvothermal process. The surface morphology and microstructure of the as-prepared Cu2− x Se were characterized by various techniques. It was found that the as-synthesized Cu2− x Se has hierarchical porosity composed of mesopores and macropores, and rich active surfaces of 111 facets. A noteworthy visible-light-responsive photocatalytic discoloration of Rhodamine B was observed for the as-developed alveolate Cu2− x Se microsheets. The superior photocatalytic properties demonstrated by the as-synthesized Cu2− x Se are mainly attributed to the highly accessible active surfaces of the 111 facets and the wider light absorption range resulting from its narrower band gap.